RECLAIMING ALIENATING ENVIRONMENTS: AFRICAN AMERICAN FEMALE PRINCIPALS REFLECT TO BUILD MATH IDENTITY AND IMPLEMENT CULTURALLY RESPONSIVE COACHING - Roberts, Marie Y (East Carolina University)
In this participatory action research (PAR), I investigated how African American female principals designed and implemented culturally responsive coaching practices to support teachers who work with the collective Black students in mathematics classrooms. Often perceived to be natural outsiders to math curriculum, mathematics classrooms can be alienating environments for Black students; leader and teacher identifying their math identity as students was critical to their ability to rethink leading and teaching practices. Secondly, coaching practices are typically culturally neutral and do not often take into consideration the identity and experiences of the coach or coachee. The goal of the study was to understand how school leaders can identify and act on their cultural identity as African American women school leaders to coach teachers to address inequities in instructional practices. In the participatory action and activist study, I used critical ethnographic methodology to investigate how two principals engaged, reflected on their personal math identities and leadership practices, and identified and implemented culturally responsive coaching practices. The findings of the study indicate that leader and teacher math identity is central to their understanding of their coaching and teaching practices. By focusing first on math identity, principals implemented culturally responsive coaching strategies and encouraged teacher implementation of culturally responsive practices in math classrooms. The study has implications for understanding how identity plays a central role in teacher change as they implement culturally responsive coaching practices to address instructional inequities.
Keywords: African American principals support teacher identity and coach CRP in math; African American school principals; African American women educators; African American students; Mentoring in education; Educational leadership; Mathematics--Study and teaching; Culturally relevant pedagogy; Action research in education